Contribution of Helicobacter pylori to the Inflammatory Complications of Common Variable Immunodeficiency - Motta-Raymundo, Adriana; Rosmaninho, Pedro; Santos, Diana F.; Ferreira, Ruben D.; Silva, Sara P.; Ferreira, Cristina; Sousa, Ana E.; Silva, Susana L. (Frontiers in Immunology, 2022)
Common Variable Immunodeficiency (CVID), the most prevalent symptomatic primary immunodeficiency, is frequently associated with severe inflammatory complications that determine its morbidity and mortality. We hypothesize that Helicobacter pylori (HP), a very common worldwide infection, may contribute to the clinical and immune phenotype of CVID. We stratified 41 CVID patients into HP+ (n=26) and HPneg (n=15) groups, according to previous urease breath test and/or gastric biopsies, and compared their clinical manifestations and immune profile evaluated by flow cytometry. No genetic variants with known potential impact in HP infection were found upon WES/WGS. Gastric complications were significantly more frequent in HP+ patients. Importantly, the six CVID patients with gastric cancer were infected with HP. In contrast, a significantly higher frequency of cytopenias was observed in the HPneg. Moreover, HP+ did not feature higher prevalence of organ auto-immunity, as well as of lung, liver or intestinal inflammatory manifestations. We observed the same B-cell profiles in HP+ and HPneg groups, accompanied by marked CD4 and CD8 T-cell activation, increased IFNγ production, and contraction of naïve compartments. Notably, HP+ patients featured low CD25 despite preserved Foxp3 levels in CD4 T cells. Overall, HP impact in CVID inflammatory complications was mainly restricted to the gastric mucosa, contributing to increased incidence of early onset gastric cancer. Thus, early HP screening and eradication should be performed in all CVID patients irrespective of symptoms.